MOTHERS' ANXIETY IN HAVING SEXUAL RELATIONS DURING PREGNANCY IN TPMB GAYAMAN VILLAGE, MOJOANYAR DISTRICT, MOJOKERTO REGENCY - Erfiani Mail; Farida Yuliani Fitria Edni Wari (Universitas STRADA Indonesia, 2026)
In live saven husband and wife, In the life of married couples, sex is a biological need that must be met. With sexual intercourse, households will be in harmony and peace, especially for newly married couples. Sexual intercourse will become routine almost every day. It is different when she is pregnant, sexual relations will decline. Knowing research purposes maternal anxiety in sexual intercourse during pregnancy at TPMB Gayaman Village, Mojoanyar District, Mojokerto Regency.